Lean Six Sigma Tools for Efficient Milking Processes in Small-Scale Dairy Farms - Satolo, Eduardo G. [UNESP]; Ussuna, Guilherme A. [UNESP]; Mac-Lean, Priscilla A. B. [UNESP] (Universidad Nacional de Colombia, 2023)
This research paper aims to use lean six sigma tools to handle milk in small Brazilian dairy estates. The search for efficiency in this process preponderates in all productive sectors. However, it is still not exploited in the dairy chain, specifically by small-scale producers, alt-hough milking is the main income for many of them. In Brazil, small producers are the main suppliers of the chain, and maintaining their competitiveness requires specific actions. Therefore, through the action-research method, four small producers in the center-west of the state of São Paulo, Brazil, were involved in identifying problems in their milking management process, investigating and implement-ing practical solutions. To this effect, lean tools such as flowcharts, Ishikawa diagrams, value stream mapping, and PDCA cycles were employed, and six feasible improvements were defined. The successful implementation of said improvements led to the acquisition of knowledge by small producers, who received financial returns, i.e., an increase in the amount paid per liter of milk. This research shows that, through interdisciplinarity, positive solutions to problems of different and complex natures, such as those in the dairy chain, can be obtained.
Herramientas lean six sigma para un proceso de ordeño eficiente en gran-jas lecheras de pequeña escala
Keywords: dairy farming; lean six sigma production; productivity improvement; rural management; small entrepreneurs